Enantioselective synthesis of inherently chiral sulfur-containing calix[4]arenes via chiral sulfide catalyzed desymmetrizing aromatic sulfenylation - Xin-Yu Zhang; Deng Zhu; Ren-Fei Cao; Yu-Xuan Huo; Tong-Mei Ding; Zhi-Min Chen (Nature Communications)
Abstract Inherently chiral calixarenes hold great potential for applications in chiral recognition, sensing, and asymmetric catalysis due to their unique structures. However, due to their special structures and relatively large sizes, the catalytic asymmetric synthesis of inherently chiral calixarenes is challenging with very limited examples available. Here, we present an efficient method for the enantioselective synthesis of inherently chiral sulfur-containing calix[4]arenes through the desymmetrizing electrophilic sulfenylation of calix[4]arenes. This catalytic asymmetric reaction is enabled by a chiral 1,1’-binaphthyl-2,2’-diamine-derived sulfide catalyst and hexafluoroisopropanol. Various inherently chiral sulfur-containing calix[4]arenes are obtained in moderate to excellent yields with high enantioselectivities. Control experiments indicate that the thermodynamically favored C-SAr product is formed from the kinetically favored N-SAr product and the combination of the chiral sulfide catalyst and hexafluoroisopropanol is crucially important for both enantioselectivity and reactivity.